The Relationship Between The Practice Of Giving Complementary Feeding To The Nutritional Status Of Children Under Two Years Old In Wringin Village, Wringin District, Bondowoso Regency - Ajani, Shakila Aprilia; Ruhana, Amalia (Jurnal Gizi dan Kesehatan Nusantara, 2023)
MP-ASI or more often referred to as companion ASI is a food that can be given to children from the age of 6 months. MP-ASI is performed because the nutritional content of breast milk cannot meet the needs of children. Research was conducted to determine the timing of MP-ASI delivery, the durability of MP-ASI delivery, and the responsiveness with the nutritional status of toddlers in Wringin Village, Wringin District, Bondowoso Regency. This study was conducted using a quantitative method using a cross-sectional design. This study was conducted in Wringin Village, Wringin Subdistrict, Bondowoso Regency with 68 respondents randomly obtained according to their presence at the posyandu. Data collection is done using interview techniques to find out the time information for MP-ASI provisioning. Observation techniques for obtaining data on MP-ASI provisioning, MP-ASI provisioning security, and responsive feed are applied during MP-ASI provisioning. Measurements of the anthropometry of BB, PB, and age to determine the nutritional status of toddlers. For data analysis using the chi-square test. By obtaining results, there is a relationship between the accuracy of MP-ASI in Wiringin Village and the safety of MP-ASI in Wiringin Village and the nutritional status of toddlers (p=0.01), the application of Wringin Village responsive feed and child nutrition (p=0.001). The suggestion for further researchers is to use quantitative methods for deeper research on the safety of MP-ASI provision as well as responsive MP-ASI provision to toddlers in Wringin Village, Wringin District, Bondowoso Regency.